Modeling with ontologies design patterns: credit scorecard as a case study - Jalil Elhassouni; Abderrahim El Qadi; Mehdi Bazzi; Mohamed El Haziti (Institute of Advanced Engineering and Science, 2020)
This paper proposes an ontological scorecard model for credit risk management. The purpose of credit scoring model is to reduce the possibility of potential losses with regard to issued loans. Loans are provided according to strict criteria which contain information about the client, loan structure, the purpose, repayment source and collateral. Several techniques have been used for credit risk assessment before granting a loan. Ontology design patterns is used here to enable the implementation of domain knowledge using the OWL rules and to improve the decision making process in credit monitoring. The modeling of our ontology will make the data publication simpler and graph structures intuitive, thus making its reusability and expandability easier.